2017
DOI: 10.1038/srep44276
|View full text |Cite
|
Sign up to set email alerts
|

Roles of vacuum tunnelling and contact mechanics in single-molecule thermopower

Abstract: Molecular junction is a chemically-defined nanostructure whose discrete electronic states are expected to render enhanced thermoelectric figure of merit suitable for energy-harvesting applications. Here, we report on geometrical dependence of thermoelectricity in metal-molecule-metal structures. We performed simultaneous measurements of the electrical conductance and thermovoltage of aromatic molecules having different anchoring groups at room temperature in vacuum. We elucidated the mutual contributions of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Numerous works are focused on exploring properties of the thermopower of single-molecule junctions. It was shown that the thermopower may be affected by molecular vibrations [11][12][13][14][15][16][17], by effects of molecular bridge geometry [18][19][20][21][22] by interactions between electrons participating in transport [23][24][25][26][27][28][29][30] and by photons [31]. Under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works are focused on exploring properties of the thermopower of single-molecule junctions. It was shown that the thermopower may be affected by molecular vibrations [11][12][13][14][15][16][17], by effects of molecular bridge geometry [18][19][20][21][22] by interactions between electrons participating in transport [23][24][25][26][27][28][29][30] and by photons [31]. Under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Length-dependent conductance and thermopower are usually observed and studied in junctions whose molecular linkers are chain-like structures consisting of several identical units (e.g. benzene or phenyl rings) [12,[19][20][21][22][45][46][47][48][49][50][51][52][53]. In the most of experiments, the thermopower appears to be proportional to the molecular bridge length.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the coupling of the NH 2 group to the Au electrode is as strong as the S group in a molecular junction. 25) ABT is a small conjugated molecule which has a conduction orbital (HOMO) 26) that is delocalized throughout the molecule (Fig. S4 in supplementary data).…”
Section: Resultsmentioning
confidence: 99%
“…In general, thermoelectric charge transport through molecular junctions is controlled by simultaneous driving by electric and thermal driving forces. The combined effect of these forces depends on several factors including the bridge geometry and the characteristics of its coupling to the leads [13][14][15][16][17][18][19][20][21][22][23][24] and electron-electron interactions [25][26][27][28][29][30][31][32][33][34]. Thermoelectric transport characteristics may be affected due to interaction between transmitting electrons and environmental nuclear motions [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and the effects of quantum interference [55,56].…”
Section: Introductionmentioning
confidence: 99%